SEJARAH PERAN GANDA PEREMPUAN JAWA TERHADAP SOSIAL EKONOMI DI KELURAHAN BAGAN KELADI KECAMATAN DUMAI BARAT (2001-2018) - Armeswari Haris; Bedriati Ibrahim; Asril Asril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Women farmers are women who work as farmers who grow crops and cultivate crops to obtain results that can beused alone or sold to others to earn income, so as to meet the needs of his family. The double role of women farmers is done to meet the family’s economic social. The purpose of this study is to find out 1) the early history of the dual role women, 2) to find out the shift in values in the dual role of women, 3) to find out the dual role of women in socio-economics, 4) to find out the decision making in the family. The method used in this study isqualitative and quantitativ. The data obtained from the results of the interviews are supplemented with the processed questionnaires. As for the place of research in writing this scientific paper is villages Bagan Keladi District Dumai Barat. Data collection techniques used are observations, questionnaires, interviews and documentation. The result of this study is the history of the beginning of the dual role as a women farmer when the help of the overnment came in 2001 which formed a farmer group which recruited women to be more, In the family of women who have a dual role in Kelurahan Bagan Keladi there is no shift in values in the family of women farmers. They continue to carry out functional structures in family life such as patterns of use of time and activities for the family, such as household affairs, work, socioeconomic, social activities and leisure time utilization. Women who have a dual role have a very important role on the socioeconomic family, in women's families who have a dual role in the decision making process for entry to the more dominant type of wife.Key Words: Dual Role, Women Farmers, Family’s Social Economic